Control Strategy in the Fight Again Internal Fraud (PT BPRS Kotabumi KC Bandar Lampung) - Hotman Hotman; Anggoro Sugeng; Ananto Triwibowo; Agus Alimuddin (Islamic Economics Journal, 2023)
Islamic banks that carry out their duties and functions as financial management institutions have the responsibility to maintain public trust by protecting and protecting customer money from all forms of irregularities. Moreover, irregularities are committed by people who work in Islamic banks themselves or what is known as internal fraud. PT BPRS Kotabumi, Bandar Lampung branch office, is one of the Islamic banks committed to fighting fraud. The form of the effort is to prevent it through internal control instruments. The purpose of this study is to determine the internal control at PT BPRS Kotabumi Bandar Lampung Branch Office as a strategy to prevent internal fraud. This research is a qualitative descriptive field research. Researchers use interview methods and documentation to collect the required data. The research data obtained are then analyzed by using inductive analysis techniques, namely analysis that begins with specific facts or events to draw conclusions. Based on the results of research that researchers have conducted, it can be concluded that internal control can be an instrument to prevent internal fraud. Internal control at BPRS Kotabumi Bandar Lampung branch includes four control components. The four components of control are the control environment, control activities, information and communication, and monitoring.